FAKTOR FAKTOR PENYEBAB TERJADINYA PERNIKAHAN DINI DI KOTA MATARAM - NI MADE SRI AYU TIANYAR (GANEC SWARA, 2024)
A marriage is the beginning of married life. The provisions of Law Number 1 of 1974 state that marriage is a form of physical and spiritual bond between a man and a woman as husband and wife with the aim of forming a happy family based on belief in the Almighty God. Thus, marriage is a very important thing in maintaining and continuing human existence which is based on noble values. The phenomenon of early marriage cases in Mataram City is relatively high. Data in 2017, there were 229 cases of marriage between children aged 17 – 19 years. This case increased in 2018 to 283 cases. The most effective way to prevent cases of early marriage is through community dialogue regarding the maturation of the marriage age in sub-districts. To answer this problem, an empirical research method was used with a study approach based on statutory regulations, a conceptual approach and a case approach. The types and sources of data used in this research are primary data and secondary data with data collection techniques through document study and interviews, where the data obtained will be analyzed deductively qualitatively.  Based on the results of research and discussion, it was found that the factors of young age and education will provide an illustration that the age factor is directly proportional to the level of education.  Low education, as well as a lack of supervision or control from parents and family, causes promiscuity which leads to promiscuous sexual behavior.  Likewise, the culture in society also contributes to early marriage.